1979
DOI: 10.1139/v79-329
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosulfates of palladium. Part 2. The hexakis(fluorosulfato)palladate (IV)ion and palladium(II) hexakis(fluorosulfato)metallates(IV)

Abstract: The synthesis of a number of compounds containing the hexakis(fluorosulfato)palladate(IV) anion and the cations Cs+, Ba2+,NO+, and ClO2+ is reported. All compounds are diamagnetic. Also reported is the synthesis of Pd[M(SO3F)6], where M = Pt(IV) and Sn(IV). Here, palladium(II) is found in a regular octahedral environment. Both compounds are paramagnetic, consistent with a 3A2g ground state. Curie–Weiss law behavior is found and ligand field parameters for the Pd(II) derivatives are reported. Vibrational spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
1
17
1
Order By: Relevance
“…Subsequently the first hetero-bimetallic fluorosulfates, P~" P~'~( S O~F ) , and ~d " S n '~( S 0 3 F )~ (4), were obtained with identification relying again on magnetic susceptibility studies, ligand field and vibrational spectra. The ir spectra for the Pd(I1)-Sn(IV) complex were distinctly different from those previously reported for salts of the type M;[Sn(S03F),j, with M' = K, Cs, NO, and C10, ( 3 , and an "aniso bidentate" bridging function of the fluorosulfate group, with strong bonding to Sn(1V) and weak coordination to Pd(II), producing an octahedral environment for both metallic centers was suggested (4). The polymeric nature was deduced from the lack of solubility in strongly ionizing HS03F, which is in contrast to high solubility and weakly basic behavior found for the M;[Sn(S03F)6] salts (5) as well as for Ba[Pt(S03F),I (6).…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Subsequently the first hetero-bimetallic fluorosulfates, P~" P~'~( S O~F ) , and ~d " S n '~( S 0 3 F )~ (4), were obtained with identification relying again on magnetic susceptibility studies, ligand field and vibrational spectra. The ir spectra for the Pd(I1)-Sn(IV) complex were distinctly different from those previously reported for salts of the type M;[Sn(S03F),j, with M' = K, Cs, NO, and C10, ( 3 , and an "aniso bidentate" bridging function of the fluorosulfate group, with strong bonding to Sn(1V) and weak coordination to Pd(II), producing an octahedral environment for both metallic centers was suggested (4). The polymeric nature was deduced from the lack of solubility in strongly ionizing HS03F, which is in contrast to high solubility and weakly basic behavior found for the M;[Sn(S03F)6] salts (5) as well as for Ba[Pt(S03F),I (6).…”
Section: Introductioncontrasting
confidence: 82%
“…The magnetic and spectroscopic study on the Pd"-MIV fluorosulfates and a parallel investigation of the corresponding silver(11) salts, ~g " S n ( s 0~F )~ and A g "~t ( s o , F )~ (6), suggested a magnetically dilute environment for the paramagnetic ions ~g ' + and more surprisingly pd2+, where an 3~2 , ground state is rather uncommon and only encountered in PdF3 (7)(8)(9) or related fluoro complexes. The study of Pd(II) fluorosulfate complexes suggested a closer approach to a bare pd2+ ion for M" being Sn rather than Pt or Pd (4).…”
Section: Introductionmentioning
confidence: 99%
“…HS03F, and SbF5 (18), the equipment used for reductive carbonylation reactions in HS0,F (17,22) or in a solid state -gas reaction (22), and our instrumentation to obtain vibrational spectra (18,22) have all been reported and described very recently. The synthesis of the starting material cisPt(C0)2(S03F), from Pt(SO,F), (19) and of cis-Pd(CO),(S03F)2 from Pd(SO,F), (23), is described elsewhere as well (22) …”
Section: Appendixmentioning
confidence: 99%
“…The synthesis of the corresponding palladium(I1) compound, Pd(C0)2(S03F),, from Pd(II)Pd(IV)(SO,F), (23), may be performed either in a solid -gas phase reaction according to:…”
mentioning
confidence: 99%
“…(iii) Detailed studies had revealed unusual magnetic properties in some cases, such as Pd(I1) with a 3A2, ground state (1) and Ag(I1) in both a magnetically dilute and concentrated system (2). Interesting reactivity patterns were found in other instances, e.g.…”
Section: Temperature Of 120°c (4) Metal Oxidation By Bis(fluorosulfumentioning
confidence: 99%